Returns to education across Europe: A comparative analysis for selected EU countries - Daniela Glocker; Viktor Steiner (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2011)
Incentives to invest in higher education are affected by both the direct wage effect of human capital investments and the indirect wage effect resulting from lower unemployment risks and shorter spells in unemployment associated with higher educated. We analyse the returns to education in Austria, Germany, Italy, Sweden and the United Kingdom, countries which differ significantly regarding both their education systems and labour market structure. We estimate augmented Mincerian wage equations accounting for the effects of unemployment on individual wages using EU-SILC data. Across countries we find a high variation of the effect of education on unemployment duration. Overall, the returns to education are estimated to be the highest in the UK, and the lowest for Sweden. A wage decrease due to time spent in unemployment results in a decline in the hourly wages in Austria, Germany and Italy.
Keywords: I21; J31; H42; 330; Returns to education; unemployment; EU-SILC